Positive electrode composite material, preparation method thereof and lithium ion battery
By introducing alumina cladding layer and island-like metal oxides in the positive electrode composite material, combined with sintering treatment, the stability and performance problems caused by high LiOH content in the positive electrode material are solved, and a higher interface is achieved Stability and battery performance.
Patent Information
- Application Number
- CN202411523049.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-29
- Publication Date
- 2025-02-07
AI Technical Summary
In the prior art, the high LiOH content in the positive electrode material leads to poor air stability and easy formation of Ni-O lithosaline phase, which leads to poor circulation stability and rate performance of lithium-ion batteries.
A positive electrode composite material is provided, which includes a core and an alumina cladding coated on the surface of the core, the core having the general formula LiNixCoyMnzO2, the alumina cladding is formed from in situ thermal decomposition of aluminum carbonate and distributed island-like on the surface. Metal oxide, LiOH content is reduced by sintering treatment.
It improves the interface stability of the positive electrode composite material, reduces the gas production risk of lithium-ion batteries during the circulation process, enhances the rate performance and cycle stability, and inhibits the formation of Ni-O rock salt phase.
Smart Images

Figure CN119400825A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode composite material, a preparation method thereof and a lithium ion battery. Background Art
[0002] Lithium-ion batteries are currently commonly used energy storage and conversion devices, and are widely used in 3C electronic products, power batteries, energy storage and other fields. They have the advantages of high energy density, low cost, environmental friendliness, and long cycle life. In response to the market users' demand for increasing battery capacity, we developed a high-nickel ternary cathode material LiNi with higher energy density. x Co y Mn 1-x-y O2 (x ≥ 0.8) is imminent, but most high-nickel ternary materials have lithium salt (LiOH) residues during the synthesis process. The residual lithium salt will not only increase the pH of the slurry, affect the processing performance, and make the material easy to gel, but also LiOH will easily react with CO2 in the air to generate water, increasing the risk of gas production during the cycle and reducing the electrochemical stability and safety of the battery.
[0003] The water washing method is currently the most commonly used method to remove residual lithium from the surface of high-nickel ternary positive electrode materials, which includes introducing additives or weak acid substances during the water washing process. The existing document (publication number 116646507A) discloses a method for preparing a high-nickel ternary positive electrode material, which is to introduce an appropriate amount of water mist into the high-nickel material during high-speed stirring, so that the water mist forms a water film on the surface of the high-nickel material to dissolve the residual alkali on the surface, and then add a large-particle water-absorbing molecular sieve material thereto, and absorb the water containing the residual alkali through the molecular sieve under low-speed stirring, and then separate the high-nickel material and the molecular sieve material through a sieve, thereby achieving a high-nickel ternary positive electrode material with low residual alkali content on the basis of low water consumption without high-temperature drying. However, the water washing process in this method will cause some Li + / H + Exchange consumes the active Li in the lattice and generates a thicker Ni-O rock salt phase, which leads to a decrease in the rate performance and cycle performance of the material. In addition, the water washing method is time-consuming and energy-intensive, and wastewater treatment also increases costs.
[0004] In summary, researching and developing a positive electrode composite material with low residual LiOH content on the surface, high interface stability, and easy processing to form a stable positive electrode slurry is of great significance for improving the rate performance and cycle stability of lithium-ion batteries. Summary of the invention
[0005] The main object of the present invention is to provide a cathode composite material, a preparation method thereof, and a lithium ion battery, so as to solve the problems in the prior art that the content of LiOH in the cathode material is high, it is easy to react with carbon dioxide in the air to generate water, resulting in poor air stability of the cathode material, and it is easy to form a Ni-O rock salt phase, thereby leading to poor cycle stability and rate performance of the lithium ion battery.
[0006] To achieve the above object, on the one hand, the present invention provides a cathode composite material, which includes: a core and an aluminum oxide coating layer coated on the surface of the core. The core has the general formula LiNi x Co y Mn z O2, where x + y + z = 1, 0.8 ≤ x < 1, 0 < y + z ≤ 0.2, 0 < y < 0.2, and the aluminum oxide coating layer is formed by in-situ thermal decomposition of aluminum carbonate during the preparation process.
[0007] Further, island-shaped distributed metal oxides are further provided on the surface of the aluminum oxide coating layer away from the core.
[0008] Further, the metal oxide includes a metal element, and the metal element is selected from one or more elements in the group consisting of elements in Group IIIB, Group IVB, and Group VIB; preferably, the metal element is selected from one or more elements in the group consisting of Zr, W, Mo, Ti, Y, and Ce elements; preferably, the metal element is Ce element, or a combination of Ce and Zr, or a combination of Ce and W; preferably, the metal element is a combination of Ce and Zr, and the weight ratio of Ce to Zr is (0.1 - 10):1; preferably, the metal element is a combination of Ce and W, and the weight ratio of Ce to W is (0.1 - 10):1.
[0009] Further, the weight ratio of the core to the metal oxide is 1:(0.00012 - 0.0037).
[0010] Further, the average particle size of the core is 1 - 5 μm, preferably 2 - 4 μm.
[0011] Further, the thickness of the aluminum oxide coating layer is 5 - 100 nm; preferably, the weight ratio of the core to the aluminum oxide coating layer is 1:(0.0004 - 0.01).
[0012] Further, the LiOH content of the cathode composite material ≤ 0.2 wt%.
[0013] On the second aspect, the present application also provides a preparation method of the above cathode composite material provided by the present application. The preparation method includes: sintering a precursor, a lithium salt, and aluminum carbonate to obtain the cathode composite material; wherein, the precursor has the general formula Ni x Co y Mnz (OH)2, wherein x, y, and z have the same definitions as in the previous text; the lithium salt is LiOH·H2O; the sintering treatment includes a first sintering treatment and a second sintering treatment, the temperature of the second sintering treatment is ≥900°C, the temperature of the second sintering treatment is higher than the temperature of the first sintering treatment, and the absolute value of the temperature difference between the two is ≥50°C.
[0014] Furthermore, the molar ratio of the precursor, the lithium salt and the aluminum carbonate is 1:(1.02-1.10):(0.0005-0.012).
[0015] Furthermore, the preparation method also includes: sintering the precursor, lithium salt, aluminum carbonate and additives to obtain a positive electrode composite material.
[0016] Further, the additive is selected from one or more oxides formed by elements in Group IIIB, Group IVB, and Group VIB; preferably, the additive is selected from one or more of the group consisting of ZrO2, WO3, MoO3, TiO2, Y2O3 and CeO2.
[0017] Furthermore, the molar ratio of the additive to the precursor is (0.00004-0.0018):1.
[0018] Furthermore, the D50 of aluminum carbonate is 1 to 3 μm.
[0019] Furthermore, the temperature of the first stage sintering treatment is 750-850°C, the heating rate is 1-10°C / min, and the time is 4-6h.
[0020] Furthermore, the temperature of the second sintering treatment is 900-950°C, the heating rate is 1-5°C / min, and the time is 3-4h.
[0021] Furthermore, the first sintering treatment and the second sintering treatment are both carried out in an oxygen atmosphere; preferably, the purity of the oxygen atmosphere is ≥99.2 vol%.
[0022] Furthermore, the preparation method before sintering also includes: using a mixer to perform a first mixing of the precursor, lithium salt and aluminum carbonate to obtain a first mixed material; sintering the first mixed material to obtain a positive electrode composite material; preferably, the rotation speed of the first mixing process is 200-1000r / min, and the time is 2-3h.
[0023] Furthermore, the preparation method before sintering also includes: using a mixer to perform a second mixing of the precursor, lithium salt, aluminum carbonate and additive to obtain a second mixed material; sintering the second mixed material to obtain a positive electrode composite material; preferably, the rotation speed of the second mixing process is 200-1000r / min, and the time is 2-3h.
[0024] The third aspect of the present application also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the positive electrode comprises the above-mentioned positive electrode composite material provided in the present application.
[0025] The traditional method of using water washing process to remove residual alkali in the positive electrode material is easy to cause Li + / H + The active Li is lost due to the exchange of the active Li, and a thick Ni-O rock salt phase is easily formed on the surface of the material. The application of the material in lithium-ion batteries will result in poor rate performance and cycle stability of the lithium-ion batteries. x Co y Mn z O2, and x, y, and z are respectively in the above-mentioned specific ranges. The nickel content of the core having the above-mentioned general formula is relatively high, which can improve the energy density of the positive electrode composite material, thereby improving the specific capacity of the lithium-ion battery. During the sintering process, Al2(CO3)3 can undergo a thermal decomposition reaction in situ to obtain Al2O3 and CO2, and Al2O3 is coated on the surface of the core to form an aluminum oxide coating layer. The generated CO2 can react with LiOH, thereby reducing the LiOH content on the surface of the positive electrode composite material, inhibiting the LiOH on the surface of the positive electrode composite material from reacting with CO2 in the air to generate water during the cycle of the lithium-ion battery, inhibiting the reaction of water with the electrolyte to generate HF and corroding the positive electrode composite material, thereby improving the interface stability of the positive electrode composite material, reducing the risk of gas production during the cycle of the lithium-ion battery, and improving its cycle stability; at the same time, it can also inhibit the formation of Ni-O rock salt phase, reduce the resistance of lithium ions to migrate at the material interface, thereby improving the rate performance of the lithium-ion battery. The setting of the alumina coating layer can inhibit the corrosion of the electrolyte to the inner core, inhibit the side reaction between the positive electrode composite material and the electrolyte, and improve the interface stability of the positive electrode composite material, thereby inhibiting the increase of the interface impedance of the positive electrode composite material during the cycle process, and further improving the rate performance and cycle stability of the lithium-ion battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0026] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0027] Figure 1 The scanning electron microscope image (SEM image) of the positive electrode composite material prepared in Example 1 of the present application is shown;
[0028] Figure 2The scanning electron microscope image (SEM image) of the positive electrode material prepared in Comparative Example 1 of the present application is shown;
[0029] Figure 3 The specific capacity-voltage curve of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 during the first charge and discharge at a rate of 0.2C is shown;
[0030] Figure 4 The change diagram of the capacity retention rate within 100 cycles of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 is shown;
[0031] Figure 5 The rate performance curve diagram of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 is shown. Detailed implementation manners
[0032] It should be noted that, without conflict, the embodiments in the present application and the features in the embodiments can be combined with each other. The present invention will be described in detail below with reference to the embodiments.
[0033] As described in the background art, the existing positive electrode materials have the problems of high content of LiOH, easy reaction with carbon dioxide in the air to generate water, resulting in poor air stability of the positive electrode materials, and easy formation of Ni-O rock salt phase, thereby leading to poor cycle stability and rate performance of lithium-ion batteries. To solve the above technical problems, in the first aspect of the present application, a positive electrode composite material is provided, which includes: a core and an alumina coating layer coated on the surface of the core. The core has the general formula LiNi x Co y Mn z O2, where x + y + z = 1, 0.8 ≤ x < 1, 0 < y + z ≤ 0.2, 0 < y < 0.2, and the alumina coating layer is formed by in-situ thermal decomposition of aluminum carbonate during the preparation process.
[0034] The traditional method of removing residual alkali in the positive electrode material by the water washing process is likely to cause Li + / H + exchange, loss of active Li, and easy formation of a relatively thick Ni-O rock salt phase on the material surface. Applying it to lithium-ion batteries will result in poor rate performance and cycle stability of the lithium-ion batteries. However, the positive electrode composite material provided in the present application includes a core and an alumina coating layer coated on the surface of the core, where the core has the general formula LiNi x Co y Mn zO2, and x, y, and z are respectively in the above-mentioned specific ranges. The nickel content of the core having the above-mentioned general formula is relatively high, which can improve the energy density of the positive electrode composite material, thereby improving the specific capacity of the lithium-ion battery. During the sintering process, Al2(CO3)3 can undergo a thermal decomposition reaction in situ to obtain Al2O3 and CO2, and Al2O3 is coated on the surface of the core to form an aluminum oxide coating layer. The generated CO2 can react with LiOH, thereby reducing the LiOH content on the surface of the positive electrode composite material, inhibiting the LiOH on the surface of the positive electrode composite material from reacting with CO2 in the air to generate water during the cycle of the lithium-ion battery, inhibiting the reaction of water with the electrolyte to generate HF and corroding the positive electrode composite material, thereby improving the interface stability of the positive electrode composite material, reducing the risk of gas production during the cycle of the lithium-ion battery, and improving its cycle stability; at the same time, it can also inhibit the formation of Ni-O rock salt phase, reduce the resistance of lithium ions to migrate at the material interface, thereby improving the rate performance of the lithium-ion battery. The setting of the alumina coating layer can inhibit the corrosion of the electrolyte to the inner core, inhibit the side reaction between the positive electrode composite material and the electrolyte, and improve the interface stability of the positive electrode composite material, thereby inhibiting the increase of the interface impedance of the positive electrode composite material during the cycle process, and further improving the rate performance and cycle stability of the lithium-ion battery.
[0035] In a preferred embodiment, the surface of the aluminum oxide coating layer away from the core is also provided with island-shaped metal oxides. The island-shaped metal oxides are beneficial to improving the structural stability and conductivity of the positive electrode composite material, thereby improving the electrochemical performance (such as specific capacity and rate performance) and cycle stability of the lithium ion battery.
[0036] In a preferred embodiment, the metal oxide includes metal elements, and the metal elements include but are not limited to one or more of the group consisting of elements in Group IIIB, Group IVB, and Group VIB. Compared with other types, the use of the above metal elements is conducive to the formation of core grains and the temperature of their growth within a suitable range, thereby facilitating the formation of a core with a suitable average particle size, and is also conducive to improving the conductivity of the positive electrode composite material, and is conducive to improving the structural stability of the positive electrode composite material, thereby facilitating the improvement of the electrochemical performance (such as specific capacity and rate performance) and cycle stability of the lithium ion battery.
[0037] In order to further make the formation of the core grains and the temperature of their growth within a more suitable range, and at the same time to further improve the conductivity of the positive electrode composite material, further improve the structural stability of the positive electrode composite material, and further improve the electrochemical properties (such as specific capacity and rate performance) and cycle stability of the lithium ion battery, preferably, the metal element includes but is not limited to one or more of the group consisting of Zr, W, Mo, Ti, Y and Ce elements; more preferably, the metal element is Ce element, or a combination of Ce and Zr, or a combination of Ce and W.
[0038] In order to further make the formation of the core grains and the temperature of their growth within a more suitable range, and at the same time to further improve the conductivity of the positive electrode composite material, further improve the structural stability of the positive electrode composite material, and further improve the electrochemical performance and cycle stability of the lithium ion battery, preferably, the metal element is a combination of Ce and Zr, and the weight ratio of Ce to Zr is (0.1-10):1; the metal element is a combination of Ce and W, and the weight ratio of Ce to W is (0.1-10):1.
[0039] In a preferred embodiment, the weight ratio of the core to the metal oxide is 1:(0.00012-0.0037). The weight ratio of the core to the metal oxide includes but is not limited to the above range, and limiting it within the above range is conducive to introducing a more suitable amount of metal elements and making them play a role, thereby facilitating the structural stability of the positive electrode composite material, and further facilitating the improvement of the electrochemical performance and cycle stability of the lithium-ion battery.
[0040] In a preferred embodiment, the average particle size of the core is 1 to 5 μm. The average particle size of the core includes but is not limited to the above range, and limiting it within the above range is beneficial to improving the compaction density of the positive electrode composite material, which is beneficial to improving the energy density of the positive electrode composite material, thereby improving the rate performance of the lithium ion battery.
[0041] In order to further improve the compaction density of the positive electrode composite material, further improve the energy density of the positive electrode composite material, and thus further improve the rate performance of the lithium ion battery, preferably, the average particle size of the core is 2 to 4 μm.
[0042] In a preferred embodiment, the thickness of the aluminum oxide coating layer is 5 to 100 nm. The thickness of the aluminum oxide coating layer includes but is not limited to the above range. Limiting it within the above range is beneficial to increasing the specific surface area of the positive electrode composite material, inhibiting the corrosion of the electrolyte to the inner core, inhibiting the occurrence of side reactions between the positive electrode composite material and the electrolyte, and improving the interface stability of the positive electrode composite material, thereby facilitating the inhibition of the increase of the interface impedance of the positive electrode composite material during the cycle, and further facilitating the improvement of the rate performance and cycle stability of the lithium ion battery.
[0043] In a preferred embodiment, the weight ratio of the core to the aluminum oxide coating layer is 1:(0.0004 - 0.01). The weight ratio of the core to the aluminum oxide coating layer includes but is not limited to the above range. Limiting it within the above range is conducive to the aluminum oxide coating layer playing a role, conducive to inhibiting the corrosion of the core by the electrolyte, conducive to inhibiting the occurrence of side reactions between the positive electrode composite material and the electrolyte, conducive to improving the interfacial stability of the positive electrode composite material, thereby conducive to inhibiting the increase in the interfacial impedance of the positive electrode composite material during cycling, and further conducive to improving the rate performance and cycling stability of the lithium-ion battery.
[0044] In a preferred embodiment, the LiOH content of the positive electrode composite material is ≤0.2 wt%. Compared with other ranges, limiting the LiOH content of the positive electrode composite material within the above range is conducive to inhibiting the reaction of LiOH on the surface of the positive electrode composite material with CO2 to generate water, conducive to improving the air stability of the positive electrode composite material, conducive to improving the interfacial stability of the positive electrode composite material, and thus conducive to improving the cycling stability of the lithium-ion battery.
[0045] The second aspect of the present application also provides a preparation method of the above positive electrode composite material, and the preparation method includes: sintering a precursor, a lithium salt and aluminum carbonate to obtain the positive electrode composite material; wherein, the precursor has the general formula Ni x Co y Mn z (OH)2, where x + y + z = 1, 0.8 ≤ x < 1, 0 < y + z ≤ 0.2, 0 < y < 0.2; the lithium salt is LiOH·H2O; the sintering treatment includes a first-stage sintering treatment and a second-stage sintering treatment, the temperature of the second-stage sintering treatment is ≥900 °C, the temperature of the second-stage sintering treatment is higher than that of the first-stage sintering treatment, and the absolute value of the temperature difference between the two is ≥50 °C.
[0046] The traditional method of using a water washing process to remove residual alkali in the positive electrode material is likely to cause Li + / H + exchange and loss of active Li, and a relatively thick Ni-O rock salt phase is easily formed on the material surface. Applying it to a lithium-ion battery will result in poor rate performance and cycling stability of the lithium-ion battery, and its removal rate of residual alkali on the material surface is low, making the pH value of the material relatively high, and the viscosity increases rapidly during the subsequent preparation of the positive electrode slurry, losing fluidity and resulting in gelation.
[0047] However, the preparation method of the positive electrode composite material provided in the present application includes: sintering the precursor, lithium salt and aluminum carbonate to obtain the positive electrode composite material. The sintering process includes two stages of sintering and the temperature difference between the two stages of sintering is within the above range, wherein, during the first stage of sintering, a crystal nucleus can be formed and gradually grows, which is convenient for the subsequent preparation of the inner core, and during the second stage of sintering, Al2(CO3)3 undergoes a thermal decomposition reaction under the above specific temperature conditions to obtain Al2O3 and CO2.
[0048] The precursor has the general formula Ni x Co y Mn z (OH)2, and x, y, and z are respectively within the above-mentioned specific ranges. The positive electrode composite material prepared using the precursor having the above-mentioned general formula is a high-nickel ternary positive electrode composite material, which itself has excellent electrochemical properties.
[0049] Compared with other types of lithium salts, the lithium salt LiOH·H2O used in this application has a lower melting point of only 471°C, which can reduce the sintering temperature and Li + / Ni 2+ The degree of mixing can be increased, and the structural stability of the positive electrode composite material can be improved, thereby improving the cycle stability of the lithium-ion battery. Moreover, during the sintering process, the molten lithium salt can be mixed with the precursor more evenly, which can reduce the lithium residue on the surface of the obtained core.
[0050] During the sintering process, Al2(CO3)3 undergoes the following thermal decomposition reaction: Al2(CO3)3→Al2O3+3CO2(g) to obtain Al2O3 and CO2. The generated CO2 can react in situ with the LiOH remaining on the surface of the inner core as follows: 2LiOH+CO2→Li2CO3+H2O(g) to obtain Li2CO3 and H2O, thereby consuming the LiOH remaining on the surface of the inner core in situ. At the same time, due to the high sintering temperature, the H2O generated in the above reaction process can evaporate quickly and will not produce bound water with the positive electrode composite material. By adopting the above-mentioned preparation method of the present application, on the one hand, the LiOH content on the surface of the positive electrode composite material can be reduced, the reaction of LiOH on the surface of the positive electrode composite material with CO2 in the air to generate water during the cycle of the lithium-ion battery can be inhibited, and the reaction of water with the electrolyte to generate HF and corrode the positive electrode composite material can be inhibited, thereby improving the interface stability of the positive electrode composite material, reducing the risk of gas production in the lithium-ion battery during the cycle, and improving its cycle stability. At the same time, it can also inhibit the formation of Ni-O rock salt phase and reduce the resistance of lithium ion migration at the material interface, thereby improving the rate performance of the lithium-ion battery; on the other hand, the Al2O3 obtained by the thermal decomposition reaction of Al2(CO3)3 can be in-situ coated on the surface of the inner core to form an alumina coating layer, which can inhibit the corrosion of the inner core by the electrolyte, inhibit the side reaction between the positive electrode composite material and the electrolyte, and improve the interface stability of the positive electrode composite material, thereby inhibiting the increase of the interface impedance of the positive electrode composite material during the cycle, and then can improve the electrochemical performance (such as specific capacity and rate performance) and cycle stability of the lithium-ion battery.
[0051] In a preferred embodiment, the molar ratio of the precursor, the lithium salt and the aluminum carbonate is 1:(1.02-1.10):(0.0005-0.012). The molar ratio of the precursor, the lithium salt and the aluminum carbonate includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the utilization rate of each raw material, thereby improving the yield of the inner core and reducing the residual LiOH on the surface of the inner core. On the other hand, it is beneficial to improve the reaction efficiency of the thermal decomposition reaction of Al2(CO3)3, and to improve the yield of Al2O3 and CO2, thereby facilitating the in-situ formation of an aluminum oxide coating layer, and reducing the LiOH content on the surface of the positive electrode composite material, thereby improving the interface stability of the positive electrode composite material, and further improving the cycle stability and rate performance of the lithium ion battery.
[0052] In a preferred embodiment, the preparation method further comprises: sintering the precursor, lithium salt, aluminum carbonate and additive to obtain a positive electrode composite material. The introduction of additives by the above method is conducive to reducing the temperature required for the precursor and lithium salt to react to form the inner core, so that the temperature of the formation of the inner core grains and their growth is within a more suitable range, and is also conducive to improving the conductivity and structural stability of the positive electrode composite material, thereby improving the electrochemical performance (such as specific capacity and rate performance) and cycle stability of the lithium ion battery; during the sintering process, due to the difference in surface energy, the additive migrates and diffuses, thereby forming an island-shaped distribution of metal oxides on the surface of the aluminum oxide coating layer away from the inner core.
[0053] In a preferred embodiment, the additive includes, but is not limited to, one or more oxides formed by elements in Group IIIB, Group IVB, and Group VIB; preferably one or more of the group consisting of ZrO2, WO3, MoO3, TiO2, Y2O3, and CeO2. Compared with other types, the use of the above-mentioned types of additives is conducive to further reducing the temperature required for the precursor to react with the lithium salt to form the core, further making the formation of the core grains and the temperature of their growth within a more suitable range, and at the same time, it is also conducive to further improving the conductivity and structural stability of the positive electrode composite material, thereby further improving the electrochemical performance (such as specific capacity and rate performance) and cycle stability of the lithium-ion battery.
[0054] In order to further reduce the temperature required for the reaction of the precursor and the lithium salt to form the inner core, further make the formation of the inner core grains and the temperature of their growth within a more suitable range, and further improve the conductivity and structural stability of the positive electrode composite material, thereby further improving the electrochemical performance and cycle stability of the lithium-ion battery, preferably, the molar ratio of the additive to the precursor is (0.00004-0.0018):1.
[0055] In a preferred embodiment, the D50 of aluminum carbonate is 1 to 3 μm. The D50 of aluminum carbonate includes but is not limited to the above range, and limiting it within the above range is beneficial to increasing the specific surface area of aluminum carbonate, and is beneficial to improving the reaction efficiency of the thermal decomposition reaction of aluminum carbonate, thereby helping to increase the yield of Al2O3 and CO2.
[0056] In a preferred embodiment, the temperature of the first sintering treatment is 750-850°C, the heating rate is 1-10°C / min, and the time is 4-6h. The temperature, heating rate and time of the first sintering treatment include but are not limited to the above ranges. Limiting them within the above ranges is conducive to the formation of crystal nuclei and the gradual growth of crystal nuclei, thereby improving the yield of the inner core and reducing Li + / Ni 2+The degree of mixing is beneficial to improving the electrochemical performance and structural stability of the positive electrode composite material, thereby helping to improve the electrochemical performance and cycle stability of lithium-ion batteries.
[0057] In a preferred embodiment, the temperature of the second sintering treatment is 900-950°C, the heating rate is 1-5°C / min, and the time is 3-4h. The temperature, heating rate and time of the second sintering treatment include but are not limited to the above ranges. Limiting them within the above ranges is conducive to improving the reaction efficiency of the thermal decomposition reaction of aluminum carbonate, and is conducive to improving the yield of Al2O3 and CO2, thereby facilitating the in-situ formation of an aluminum oxide coating layer, and is conducive to reducing the LiOH content on the surface of the positive electrode composite material, thereby facilitating improving the interface stability of the positive electrode composite material, and is conducive to improving the cycle stability and rate performance of lithium-ion batteries.
[0058] In a preferred embodiment, the first sintering treatment and the second sintering treatment are both carried out in an oxygen atmosphere. Compared with other atmospheres, carrying out the first sintering treatment and the second sintering treatment in an oxygen atmosphere is conducive to reducing the temperature required for the sintering treatment, improving the efficiency of the oxidation of the precursor during the sintering process, and improving the reaction efficiency of the thermal decomposition reaction of aluminum carbonate. It is also conducive to reducing the introduction of impurities and improving the purity of the positive electrode composite material, thereby improving the electrochemical performance and structural stability of the prepared positive electrode composite material.
[0059] In order to further reduce the temperature required for sintering treatment, further improve the efficiency of the oxidation of the precursor during the sintering process, further improve the reaction efficiency of the thermal decomposition reaction of aluminum carbonate, and at the same time to further improve the purity of the positive electrode composite material, preferably, the purity of the oxygen atmosphere is ≥99.2 vol%.
[0060] In a preferred embodiment, the preparation method before sintering further includes: using a mixer to first mix the precursor, lithium salt and aluminum carbonate to obtain a first mixed material; and sintering the first mixed material to obtain a positive electrode composite material. Using a mixer to first mix the precursor, lithium salt and aluminum carbonate is beneficial to improving their dispersibility, improving the efficiency of subsequent sintering treatment, reducing costs, and facilitating obtaining a positive electrode composite material.
[0061] In order to further improve the dispersibility of the precursor, lithium salt and aluminum carbonate, and further improve the efficiency of the subsequent sintering treatment, preferably, the rotation speed of the first mixing process is 200-1000 r / min, and the time is 2-3 h.
[0062] In a preferred embodiment, before the sintering treatment, the preparation method further comprises: using a mixer to perform a second mixing of the precursor, lithium salt, aluminum carbonate and additives to obtain a second mixed material; and sintering the second mixed material to obtain a positive electrode composite material. Using a mixer to perform a second mixing of the precursor, lithium salt, aluminum carbonate and additives is beneficial to improving their dispersibility, improving the efficiency of the subsequent sintering treatment, reducing costs, and facilitating the preparation of a positive electrode composite material.
[0063] In order to further improve the dispersibility of the precursor, lithium salt, aluminum carbonate and additives, and further improve the efficiency of the subsequent sintering process, preferably, the rotation speed of the second mixing process is 200-1000 r / min, and the time is 2-3 h.
[0064] In a preferred embodiment, the preparation method of the precursor in the present application comprises: mixing nickel salt, cobalt salt and manganese salt with water to prepare a metal salt solution, wherein the molar ratio of nickel element in the nickel salt, cobalt element in the cobalt salt and manganese element in the manganese salt is x:y:z; using NaOH solution as a precipitant and ammonia water as a complexing agent; mixing the metal salt solution, the complexing agent and the precipitant, reacting under a nitrogen atmosphere, controlling the reaction temperature within 40 to 80° C., controlling the pH value of the reaction solution between 10.5 and 12.5, adjusting the stirring speed and the pumping speed of each component during the reaction, stopping the reaction until the target particle size range is obtained, and aging, washing, separating and drying in sequence after the reaction is completed to obtain Ni x Co y Mn z (OH)2 precursor.
[0065] The third aspect of the present application also provides a lithium-ion battery, comprising a positive electrode, a negative electrode, an electrolyte, and a separator arranged between the positive electrode and the negative electrode, wherein the positive electrode comprises the positive electrode composite material provided in the present application.
[0066] The above-mentioned positive electrode composite material provided in the present application has a low LiOH content on the surface, which can inhibit the LiOH on the surface of the positive electrode composite material from reacting with CO2 in the air to generate water during the cycle of the lithium-ion battery, and inhibit the reaction of water with the electrolyte to generate HF and corrode the positive electrode composite material. At the same time, it can also inhibit the formation of Ni-O rock salt phase, reduce the resistance of lithium ion migration at the material interface, thereby improving the cycle stability and rate performance of the lithium-ion battery; during the sintering process, the Al2O3 obtained by the thermal decomposition reaction of Al2(CO3)3 can be in-situ coated on the surface of the inner core to form an alumina coating layer, which can inhibit the corrosion of the inner core by the electrolyte, inhibit the side reaction between the positive electrode composite material and the electrolyte, and improve the interface stability of the positive electrode composite material, thereby inhibiting the increase of the interface impedance of the positive electrode composite material during the cycle, and then can improve the rate performance and cycle stability of the lithium-ion battery; at the same time, due to the low LiOH content on the surface of the above-mentioned positive electrode composite material, it is not easy to gel when preparing the positive electrode slurry, which is convenient for processing to obtain a lithium-ion battery.
[0067] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0068] Example 1
[0069] A method for preparing a positive electrode composite material comprises the following steps:
[0070] (1) Preparing a precursor: NiSO4·6H2O, CoSO4·7H2O and MnSO4·H2O were mixed with 100 mL of water at a molar ratio of 90:5:5 to prepare a metal salt solution with a concentration of 2 mol / L; a 4 mol / L NaOH solution was used as a precipitant, and a 2 mol / L ammonia solution was used as a complexing agent; the metal salt solution, the complexing agent and the precipitant were mixed and reacted under a nitrogen atmosphere, the reaction temperature was controlled within a range of 40 to 80° C., the pH value of the reaction solution was controlled between 10.5 and 12.5, the stirring speed and the pumping speed of each component were adjusted during the reaction, and the reaction was stopped until the target particle size range was obtained. After the reaction was completed, the Ni 0.90 Co 0.05 Mn 0.05 (OH)2 precursor;
[0071] (2) 1000g Ni 0.90 Co 0.05 Mn 0.05 (OH)2 precursor, 464.81g LiOH·H2O, 12.65g Al2(CO3)3 and 2gCeO2 were mixed in a high-speed mixer at a speed of 400r / min for 2h to obtain a mixed material;
[0072] (3) The mixed material is subjected to a first sintering treatment and a second sintering treatment in sequence in an oxygen atmosphere with a purity of 99.5 vol%, wherein the temperature of the first sintering treatment is 820°C, the heating rate is 2°C / min, and the time is 6 hours, and the temperature of the second sintering treatment is 930°C, the heating rate is 2°C / min, and the time is 3 hours. After the second sintering treatment is completed, it is cooled to room temperature to obtain a positive electrode composite material.
[0073] The positive electrode composite material prepared in Example 1 includes, from the inside to the outside, a core, an aluminum oxide coating layer, and cerium oxide distributed in an island shape on the surface of the aluminum oxide coating layer, wherein the core is LiNi 0.90 Co 0.05 Mn 0.05 O2, the average particle size of the core is 3 μm, the thickness of the aluminum oxide coating is 20 nm, and the weight ratio of cerium oxide to the core is 0.0019:1.
[0074] Depend on Figure 1 It can be seen that the positive electrode composite material prepared in Example 1 has irregular block-shaped particles, retaining the original angular grain structure of the inner core, and its surface is relatively rough, which is formed by the deposition of Al2O3 produced by the thermal decomposition reaction of aluminum carbonate and the additive cerium oxide on the surface of the inner core.
[0075] Example 2
[0076] The difference from Example 1 is that the molar ratio of the precursor to aluminum carbonate in step (2) is 1:0.0005, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the thickness of the aluminum oxide coating layer is 5 nm.
[0077] Example 3
[0078] The difference from Example 1 is that the molar ratio of the precursor to aluminum carbonate in step (2) is 1:0.012, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the thickness of the aluminum oxide coating layer is 50 nm.
[0079] Example 4
[0080] The difference from Example 1 is that the molar ratio of the precursor to aluminum carbonate in step (2) is 1:0.02, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the thickness of the aluminum oxide coating layer is 100 nm.
[0081] Example 5
[0082] The difference from Example 1 is that the molar ratio of the precursor to the additive in step (2) is 1:0.00004, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the average particle size of the core is 3 μm, and the weight ratio of cerium oxide to the core is 0.00012:1.
[0083] Example 6
[0084] The difference from Example 1 is that the molar ratio of the precursor to the additive in step (2) is 1:0.0018, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the average particle size of the core is 3 μm, and the weight ratio of cerium oxide to the core is 0.0037:1.
[0085] Example 7
[0086] The difference from Example 1 is that the molar ratio of the precursor to the additive in step (2) is 1:0.003, and the remaining steps are the same as Example 1. In the prepared positive electrode composite material, the average particle size of the core is 5.5 μm, and the weight ratio of cerium oxide to the core is 0.0053:1.
[0087] Example 8
[0088] The difference from Example 1 is that the additive in step (2) is replaced by an additive composition of equal amounts of CeO2 and WO3, wherein the weight ratio of CeO2 to WO3 is 1:1, and the remaining steps are the same as those in Example 1. The prepared positive electrode composite material comprises, from the inside to the outside, a core, an alumina coating layer, and cerium oxide and tungsten oxide distributed in islands on the surface of the alumina coating layer, wherein the average particle size of the core is 3 μm, and the weight ratio of the total weight of cerium oxide and tungsten oxide to the core is 0.0022:1.
[0089] Example 9
[0090] The difference from Example 1 is that the additive in step (2) is replaced by an additive composition of equal amounts of CeO2 and WO3, wherein the weight ratio of CeO2 to WO3 is 1:20, and the remaining steps are the same as those in Example 1. The prepared positive electrode composite material comprises, from the inside to the outside, a core, an alumina coating layer, and cerium oxide and tungsten oxide distributed in islands on the surface of the alumina coating layer, wherein the average particle size of the core is 3 μm, and the weight ratio of the total weight of cerium oxide and tungsten oxide to the core is 0.0038:1.
[0091] Example 10
[0092] The difference from Example 1 is that the temperature of the first sintering treatment is 750° C. and the time is 6 hours, the temperature of the second sintering treatment is 950° C. and the time is 3 hours, and the remaining steps are the same as Example 1.
[0093] Embodiment 11
[0094] The difference from Example 1 is that the temperature of the first sintering treatment is 850° C. and the time is 4 hours, the temperature of the second sintering treatment is 900° C. and the time is 4 hours, and the remaining steps are the same as Example 1.
[0095] Example 12
[0096] The difference from Example 1 is that the temperature of the first sintering process is 700° C., and the remaining steps are the same as Example 1.
[0097] Embodiment 13
[0098] The difference from Example 1 is that the temperature of the first sintering process remains unchanged, the temperature of the second sintering process is 850° C., and the remaining steps are the same as Example 1.
[0099] Comparative Example 1
[0100] A method for preparing a positive electrode material comprises the following steps:
[0101] (1) 1000g Ni 0.90 Co 0.05 Mn 0.05 The (OH)2 precursor, 464.81 g of LiOH·H2O and 2 g of CeO2 were mixed in a high-speed mixer at a rotation speed of 400 r / min for 2 h to obtain a mixed material;
[0102] (2) sintering the mixture in an oxygen atmosphere with a purity of 99.5%, wherein the sintering temperature is 820° C., the heating rate is 2° C. / min, and the time is 3 h. After the sintering, the mixture is cooled to room temperature to obtain a product to be washed;
[0103] (3) The product to be washed is placed in a water washing kettle, washed with 10° C. water for 4 h, and then filtered and dried in sequence to obtain a positive electrode material, wherein the drying temperature is 80° C. and the drying time is 12 h.
[0104] The positive electrode material prepared in Comparative Example 1 includes a core and cerium oxide distributed in an island shape on the surface of the core, wherein the core is LiNi 0.90 Co 0.05 Mn 0.05 O2, and its particle size is 4μm, and the weight ratio of cerium oxide to the core is 0.0019:1.
[0105] Depend on Figure 2 It can be seen that the positive electrode material prepared in Comparative Example 1 has irregular block-shaped particles and a relatively smooth surface. This is because water washing destroys the interfacial stability of the positive electrode material and forms more Ni-O rock salt phases on the surface of the positive electrode material, resulting in a relatively smooth surface.
[0106] The positive electrode composite materials prepared in the above-mentioned Examples 1 to 13 of the present application and the positive electrode material prepared in Comparative Example 1 were tested as follows:
[0107] (1) Detection of LiOH and Li2CO3 content on the material surface
[0108] Weigh 5 g of the positive electrode composite materials prepared in Examples 1 to 13 and the positive electrode material prepared in Comparative Example 1, respectively, dissolve them in 100 mL of deionized water, stir at a rate of 800 r / min for 5 min, and perform solid-liquid separation by vacuum filtration to obtain a filtrate. The weight of the filtrate is weighed and recorded as m. The obtained filtrate is placed in a potentiometric titrator (Metrohm, 905T), and titrated with a 0.1 mol / L hydrochloric acid standard titration solution, wherein Ep1 (pH≈8.5) and Ep2 (pH≈4.5) are two equivalence points, and the volumes of hydrochloric acid consumed when reaching the equivalence points are recorded as V1 and V2, respectively; the mass fraction ω of lithium carbonate is calculated according to formula (1): Li2CO3 ; Calculate the mass fraction of LiOH ω according to formula (2) LiOH ;
[0109] ω Li2CO3 =[0.1(V2-V1)×100×73.89] / (1000×5×m)×100% (1);
[0110] ω LiOH =[0.1V2-2(V2-V1)×100×23.95] / (1000×5×m)×100% (2);
[0111] (2) pH value detection
[0112] Weigh 5 g of the positive electrode composite materials prepared in Examples 1 to 13 and the positive electrode material prepared in Comparative Example 1 respectively, place them in a 100 mL conical flask equipped with a magnetic stirrer, quickly seal it with a sealing film to prevent interference from CO2 in the air, place the conical flask on a magnetic stirrer, stir at a stirring rate of 800 r / min for 5 min, and then let it stand at a constant temperature of 25°C for 1 h. After calibrating the pH value of the buffer reagent to 9.18 and 12.45, read the pH value of the supernatant in the conical flask with a pH meter, and repeat the test three times in the same way.
[0113] The test results are shown in Table 1.
[0114] Table 1
[0115]
[0116] The positive electrode composite materials prepared in the above embodiments 1 to 13 of the present application and the positive electrode material prepared in comparative example 1 are respectively used as positive electrode active materials, and the positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a weight ratio of 90:5:5 to obtain a positive electrode slurry, and the above positive electrode slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode is obtained after drying; a lithium sheet is used as a negative electrode, 1 mol / L lithium hexafluorophosphate is used as an electrolyte (solvent EC+DMC, volume ratio 1:1), and polypropylene is used as a separator to assemble a button-type lithium-ion battery.
[0117] The following performance tests were performed on all lithium-ion batteries prepared in this application. The specific test methods are as follows:
[0118] (1) The test conditions for the first charge specific capacity and the first coulombic efficiency (hereinafter referred to as the first efficiency) are as follows: constant current charging at a rate of 0.2C, with a voltage range of 2.8 to 4.35V;
[0119] (2) The test conditions for the first discharge specific capacity are as follows: constant current discharge at a rate of 0.2C, with a voltage range of 2.8 to 4.35V;
[0120] (3) The test conditions for capacity retention are as follows: at 25°C, voltage range 2.8-4.35V, 100 cycles;
[0121] (4) The test conditions for the discharge specific capacity at multiple rates are as follows: in the voltage range of 2.8 to 4.35 V, constant current discharge is performed at rates of 0.2C, 0.33C, 0.5C, 1C and 2C respectively.
[0122] The performance test results are shown in Table 2. The specific capacity-voltage curves of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 for the first cycle of charge and discharge at a rate of 0.2C are shown in Table 2. Figure 3 The capacity retention rate change diagram of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 within 100 cycles is shown in FIG. Figure 4 The rate performance curves of the positive electrode composite material prepared in Example 1 of the present application and the positive electrode material prepared in Comparative Example 1 are shown in FIG. Figure 5 shown.
[0123] Table 2
[0124]
[0125] Depend on Figure 3 It can be seen that the charging capacity of the lithium-ion battery prepared in Example 1 is higher in the entire voltage range, which indicates that the interface impedance of the positive electrode composite material prepared in Example 1 is lower, which is beneficial to Li + diffusion; Figure 4It can be seen that the capacity retention rate of the lithium ion battery prepared in Example 1 after 100 cycles is higher than that in Comparative Example 1, which indicates that the positive electrode composite material prepared in Example 1 has better structural stability than the positive electrode material prepared in Comparative Example 1. Figure 5 It can be seen that the discharge capacity of the lithium ion battery prepared in Example 1 is better than that of Comparative Example 1 at all rates, especially at high rates, which indicates that the positive electrode composite material prepared in Example 1 has higher rate performance than the positive electrode material prepared in Comparative Example 1.
[0126] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0127] By comparing Example 1 and Comparative Example 1, it can be seen that the positive electrode composite material provided in the present application includes a core and an alumina coating layer coated on the surface of the core, and during the sintering process, Al2(CO3)3 can undergo in-situ thermal decomposition reaction to obtain Al2O3 and CO2, and Al2O3 is coated on the surface of the core to form an alumina coating layer. The generated CO2 can react with LiOH, thereby reducing the LiOH content on the surface of the positive electrode composite material, inhibiting the LiOH on the surface of the positive electrode composite material from reacting with CO2 in the air to generate water during the cycle of the lithium ion battery, inhibiting the reaction of water with the electrolyte to generate HF and corroding the positive electrode composite material, thereby improving the interface stability of the positive electrode composite material, reducing the risk of gas production in the cycle of the lithium ion battery, and improving its cycle stability; at the same time, it can also inhibit the formation of the Ni-O rock salt phase and reduce the resistance of lithium ions to migrate at the material interface, thereby improving the rate performance of the lithium ion battery; the provision of the alumina coating layer can inhibit the corrosion of the electrolyte to the inner core, inhibit the side reaction between the positive electrode composite material and the electrolyte, improve the interface stability of the positive electrode composite material, thereby inhibiting the increase of the interface impedance of the positive electrode composite material during the cycle, thereby improving the rate performance and cycle stability of the lithium ion battery; at the same time, the LiOH content on the surface of the above-mentioned positive electrode composite material of the present application is low, and the pH value is low. It is not easy to gel when preparing the positive electrode slurry, and it is easy to process to obtain a lithium ion battery.
[0128] Comparing Examples 1 to 4, in Example 4, due to the relative excess of aluminum carbonate, it still has a significant improvement effect on the content of LiOH and Li2CO3 on the material surface, but the surface impedance and capacity of the lithium ion battery prepared therefrom will tend to deteriorate; it can be seen that the molar ratio of the precursor to aluminum carbonate includes but is not limited to the above range. Limiting it within the above range is beneficial to improving the utilization rate of each raw material, thereby improving the yield of the inner core and reducing the LiOH residue on the surface of the inner core. On the other hand, it is beneficial to improve the reaction efficiency of the Al2(CO3)3 thermal decomposition reaction, which is beneficial to improving the yield of Al2O3 and CO2, thereby facilitating the in-situ formation of an alumina coating layer, reducing the LiOH content on the surface of the positive electrode composite material, thereby improving the interface stability of the positive electrode composite material, and then It is beneficial to improve the cycle stability and rate performance of the lithium ion battery.
[0129] By comparing Examples 1, 5 to 7, it can be seen that the molar ratio of the precursor to the additive includes but is not limited to the above range. Limiting it within the above range is beneficial to reducing the temperature required for the precursor to react with the lithium salt to form an inner core, and is beneficial to making the formation of the inner core grains and the temperature of their growth within a more suitable range. At the same time, it is beneficial to improve the electrical conductivity and structural stability of the positive electrode composite material, thereby helping to improve the electrochemical performance (specific capacity, rate performance and first efficiency) and cycle stability of lithium-ion batteries.
[0130] By comparing Examples 1, 8 and 9, it can be seen that compared with other types of additives, the use of the above-mentioned types of additives in the present application is beneficial to reducing the temperature required for the precursor to react with the lithium salt to form the inner core, which is beneficial to the formation of the inner core grains and the temperature of their growth within a more suitable range. At the same time, it is also beneficial to improve the electrical conductivity and structural stability of the positive electrode composite material, thereby improving the electrochemical properties (specific capacity, rate performance and first efficiency) and cycle stability of lithium-ion batteries.
[0131] Comparing Examples 1, 10 to 13, it can be seen that the temperature, heating rate and time of the first stage sintering treatment include but are not limited to the above ranges. Limiting them within the above ranges is conducive to the formation of crystal nuclei and the gradual growth of crystal nuclei, thereby improving the yield of the inner core and reducing Li + / Ni 2+The degree of mixing is beneficial to improving the electrochemical performance and structural stability of the positive electrode composite material, thereby helping to improve the electrochemical performance and cycle stability of the lithium-ion battery; the temperature, heating rate and time of the second sintering treatment include but are not limited to the above ranges, and limiting them within the above ranges is beneficial to improving the reaction efficiency of the thermal decomposition reaction of aluminum carbonate, and is beneficial to increasing the yields of Al2O3 and CO2, thereby facilitating the in-situ formation of an alumina coating layer, and reducing the LiOH content on the surface of the positive electrode composite material, thereby helping to improve the interface stability of the positive electrode composite material, and is beneficial to improving the cycle stability and rate performance of the lithium-ion battery.
[0132] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0133] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A positive electrode composite material, characterized in that: The positive electrode composite material includes: a core and an aluminum oxide coating layer coated on the surface of the core. The core has the general formula LiNi x Co y Mn z O2, where x + y + z = 1, 0.8 ≤ x < 1, 0 < y + z ≤ 0.2, 0 < y < 0.2, and the aluminum oxide coating layer is formed by in-situ thermal decomposition of aluminum carbonate during the preparation process.
2. The positive electrode composite material according to claim 1, characterized in that: The surface of the aluminum oxide coating layer away from the core is also provided with metal oxide distributed in island shape; Preferably, the metal oxide comprises a metal element, and the metal element is selected from one or more of the group consisting of elements in Group IIIB, Group IVB, and Group VIB; Preferably, the metal element is selected from one or more of the group consisting of Zr, W, Mo, Ti, Y and Ce elements; Preferably, the metal element is Ce, or a combination of Ce and Zr, or a combination of Ce and W; preferably, the metal element is a combination of Ce and Zr, and the weight ratio of Ce to Zr is (0.1-10):1; preferably, the metal element is a combination of Ce and W, and the weight ratio of Ce to W is (0.1-10):1; Preferably, the weight ratio of the inner core to the metal oxide is 1:(0.00012-0.0037).
3. The positive electrode composite material according to claim 1 or 2, characterized in that: The average particle size of the core is 1 to 5 μm, preferably 2 to 4 μm; Preferably, the thickness of the aluminum oxide coating layer is 5 to 100 nm; Preferably, the weight ratio of the inner core to the alumina coating layer is 1:(0.0004-0.01); Preferably, the LiOH content of the positive electrode composite material is ≤0.2 wt %.
4. A method for preparing the positive electrode composite material according to any one of claims 1 to 3, characterized in that: The preparation method comprises: The precursor, lithium salt and aluminum carbonate are sintered to obtain the positive electrode composite material; wherein the precursor has a general formula of Ni x Co y Mn z (OH)2, wherein x, y, and z have the same definitions as in claim 1; the lithium salt is LiOH·H2O; The sintering process includes a first stage sintering process and a second stage sintering process, the temperature of the second stage sintering process is ≥900°C, the temperature of the second stage sintering process is higher than the temperature of the first stage sintering process, and the absolute value of the temperature difference between the two is ≥50°C.
5. The method for preparing the positive electrode composite material according to claim 4, characterized in that: The molar ratio of the precursor, the lithium salt and the aluminum carbonate is 1:(1.02-1.10):(0.0005-0.012).
6. The method for preparing the positive electrode composite material according to claim 4 or 5, characterized in that: The preparation method further comprises: performing the sintering treatment on the precursor, the lithium salt, the aluminum carbonate and the additive to obtain the positive electrode composite material; Preferably, the additive is selected from one or more oxides formed by elements in Group IIIB, Group IVB, and Group VIB; Preferably, the additive is selected from one or more of the group consisting of ZrO2, WO3, MoO3, TiO2, Y2O3 and CeO2; Preferably, the molar ratio of the additive to the precursor is (0.00004-0.0018):1; Preferably, the D50 of the aluminum carbonate is 1 to 3 μm.
7. The method for preparing the positive electrode composite material according to any one of claims 4 to 6, characterized in that: The temperature of the first stage sintering treatment is 750-850°C, the heating rate is 1-10°C / min, and the time is 4-6h; Preferably, the temperature of the second stage sintering treatment is 900-950°C, the heating rate is 1-5°C / min, and the time is 3-4h; Preferably, the first sintering process and the second sintering process are both performed under an oxygen atmosphere; More preferably, the purity of the oxygen atmosphere is ≥99.2 vol%.
8. The method for preparing the positive electrode composite material according to claim 4 or 5, characterized in that: Before the sintering treatment, the preparation method further includes: using a mixer to first mix the precursor, the lithium salt and the aluminum carbonate to obtain a first mixed material; and performing the sintering treatment on the first mixed material to obtain the positive electrode composite material; Preferably, the rotation speed of the first mixing process is 200-1000 r / min and the time is 2-3 h.
9. The method for preparing the positive electrode composite material according to claim 6, characterized in that: Before the sintering treatment, the preparation method further includes: using a mixer to perform a second mixing on the precursor, the lithium salt, the aluminum carbonate and the additive to obtain a second mixed material; performing the sintering treatment on the second mixed material to obtain the positive electrode composite material; Preferably, the rotation speed of the second mixing process is 200-1000 r / min and the time is 2-3 h.
10. A lithium ion battery comprising a positive electrode, a negative electrode, an electrolyte, and a separator disposed between the positive electrode and the negative electrode, characterized in that: The positive electrode comprises the positive electrode composite material according to any one of claims 1 to 3.